The Dragon Tree - Hunt,Roderick (Oxford University Press, 1986)
In "ORT The Dragon Adventure" by Roderick Hunt, part of the Oxford Reading Tree series, Biff, Chip, Kipper, and their dog, Floppy, find themselves on a fantastical journey involving a dragon.
Keywords: Textbook